Maintenance management of food court in Shah Alam / Nurul Kamaliah Kamarudin - Kamarudin, Nurul Kamaliah (Faculty of Architecture, Planning and Surveying, 2015)
Ahmad et al. (2006) opined that in Malaysia, maintenance problems in buildings are common regardless of the size and owners of the buildings. Ahmad (2006) conducted a case study on 16 large properties (covering 381,804.55 m2 net floor area) owned by Pertubuhan Keselamatan Sosial (PERKESO), a government subsidiary. On the basis of his findings, he concluded that the buildings lacked adequate maintenance despite the enormous resources committed to the maintenance activities. According Noraziah (2006) a major problem faced by property developers in Malaysia was discovered to be poor collection of maintenance fees, the major reason being the dissatisfaction on the part of users with the condition of their buildings. Besides that in The Restaurant Location Guidebook by John C. Melaniphy (2007) also has listed some of the problems that often occur, one of the problems that the list was the lack of chairs and tables. The lack of chairs and tables is a critical issue for businesses in the food court. This is because of the lack of chairs and tables will give impact to sales and customers. Besides that, in The Restaurant Location Guidebook by John C. Melaniphy (2007) also reveals some of the problems that occur in the food court is seating is poor efficiency at the food court. Normally a table in the food court order a table for four people. But usually people who attended the food court is a singly or in pairs. So the table is not used as 100 percent efficiency. For that table only produces 50 percent efficiency and this differ with the use of a table for four people occupied with four people who produce 100 percent efficiency for seating. The next problem is not enough seating and space is limited. It becomes a problem for traders who trade. Trade or shop space provided small and complicate the work of business management. This can be seen in the food court at the Giant Section 13 Shah Alam. Dealers were given limited space for cooking. So due to the broad masses of dealers there sell food that is easy to sell like sizzling, buffet food and traditional food.